Black Swans Will Peck Us Apart, or On Conservative Millenarianism and Playing the Scandal Card - Bucholc, Marta (Studia Socjologiczne, 2026)
The purpose of this article is to present the concept of conservative millenarianism as an analytical tool for identifying contemporary conservative political mobilizations. The aim of the article is to revisit Karl Mannheim’s classic typology of utopias, drawing inspiration from Zygmunt Bauman’s concept of retrotopia. The author takes Mannheim’s categorization of utopian mentalities – defined by their relationship to time – as its starting point and reconfigures it to describe a hybrid form of political practice that combines the millenarian imperative of immediacy with a conservative orientation toward the past. From Mannheim’s perspective, chiliasm or millenarianism is a kind of utopian actualization of the future, whereas conservative utopia reconstructs the past as a source of renewal; the concept presented here synthesizes these two orientations into a single analytical category, useful for studying contemporary political strategies of legitimization. The article discusses three interrelated dimensions of conservative millenarianism. The first of them is the imperative of turning back. The second is the conviction that this turn not only halts the forward movement but constitutes an annulment of the historical process. Consequently, the third element emerges: the image of the future as the unchanging extension of the present. This total presentism raises immobility to the rank of an active strategy for preserving the status quo.